2015
DOI: 10.1007/s10800-015-0894-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrochemical performance of highly porous carbons by single-step potassium humate carbonization for application in supercapacitors

Abstract: This paper presents the direct synthesis of highly porous carbons via the carbonization of potassium humate in inert atmosphere without any activation. Carbonization temperature is important for carbon structures and their electrochemical performance in electric doublelayer capacitors. The CK800 material derived from potassium humate has a high-specific surface area of 890 m 2 g -1 and an ideal average pore size of 2.56 nm. The CK800 material can also deliver a high-specific capacitance of 232 F g -1 (26.1 lF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Therefore, these samples exhibit an amorphous framework in general. 35,43 With the increase of CH 3 COOK dosage, the (002) become narrow, suggesting an increase of graphitic crystalline degree.…”
Section: Microstructure and Chemical Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, these samples exhibit an amorphous framework in general. 35,43 With the increase of CH 3 COOK dosage, the (002) become narrow, suggesting an increase of graphitic crystalline degree.…”
Section: Microstructure and Chemical Compositionmentioning
confidence: 99%
“…It is found that all process results similarly yield between 33% and 36%, comparable with that of related references. 35 Elemental analyses (Table 2) were carried out to investigate the chemical compositions of ACs. It is found that the un-activated sample (sample CK-0) demonstrates an obviously low C content of 70.09 at.% and a high O content of 9.79 at.%, which possibly results in a poor electrical conductivity.…”
Section: Microstructure and Chemical Compositionmentioning
confidence: 99%
See 3 more Smart Citations